The role of tertiary education in career and life-long learning among day-time students (based on empirical findings) - Czeglédi, Csilla; Juhász, Tímea (Journal of Education Culture and Society, 2020)
There is an increased demand for education in our society. The expectations of employers and the economy in general have also changed; knowledge is fast becoming the driving force behind labour market competitiveness. Seeing these tendencies, we had to ask ourselves how the most involved group, the students see their situation. How do they see the role of educa-tion in their career paths as well as in life-long learning? We conducted our research in this fi eld in the second half of last year. In this essay, we are publishing some partial results of that research in order to prove the hypothesis made during our studies.